The Relationship Between Loneliness And Psycological Well Being With Fear Of Missing Out (Fomo) In Teenage Social Media Users At SMAN Arjasa Jember - Siti Wardatul Jannah; Niken Titi Pratitis; Mamang Effendy (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
His study aims to analyze the relationship between loneliness, psycological well being, and fear of missing out (FOMO) in adolescent social media users at SMAN Arjasa Jember. This study used a quantitative approach with a correlational design, involving 265 students selected through cluster random sampling. The results showed a significant relationship between loneliness and FOMO, as well as between psycological well being and FOMO. Adolescents who experienced higher levels of loneliness tended to have greater FOMO tendencies, while those with higher psychological well being tended to have lower levels of FOMO. These results demonstrate the importance of psychological well being and social support in mitigating the negative impact of social media on adolescents. This study provides an important contribution to the development of psychological interventions to address FOMO in adolescents.